Iconic home : interiors, advice, and stories from 50 amazing Black designers - Reese, June (Abrams, 2023)
"In 2010, Black Interior Designers, Inc. (BID) began to unite, connect, and promote Black designers, bringing their projects into the spotlight. Author Ashley June Reese lends her thoughtful eye and powerful writing to the project, weaving together inspiring interiors and the fascinating personal stories of each featured designer. Justina Blakeney, Faith Blakeney, Adair Curtis and Jason Bolden of JSN Studio, Bridgid Coulter, Corey Damen Jenkins, Forbes and Masters, General Judd, Keia McSwain, Brigette Romanek, and a total of 50 industry stars, tell their stories and share their challenges and triumphs. Design philosophies and creative influences are brought to light and mingle with wonderfully designed spaces in a range of styles: The result is a behind-the-scenes look at what it means to be a person of color creating work in the design industry today" --